Comparison of oral cavity protein abundance among caries-free and caries-affected individuals-a systematic review and meta-analysis - Eliane Garcia da Silveira; Eliane Garcia da Silveira; Laura Schaurich Prato; Sarah Freygang Mendes Pilati; Rodrigo Alex Arthur (Frontiers Media S.A., 2023)
ObjectiveSome salivary proteins seem to be differently abundant among caries-free (CF) and caries-affected (CA) individuals, but previous results are contradictory precluding that definitive conclusion be drawn. A pooled analysis of the available evidence may provide more robust data on identifying oral cavity protein patterns among CF and CA individuals. This systematic review and meta-analysis (PROSPERO CRD42021269079) aimed to compare the oral cavity protein abundance among caries-free and caries-affected individuals.MethodsThis study was conducted following PRISMA guidelines. PubMed, Embase, and Web of Science databases were systematically assessed (up to February 2023) to retrieve clinical studies written in English, German, or in Latin-based languages that compared the oral cavity protein abundance among CF and CA individuals. Data extraction and methodological quality assessment (NIH guidelines) were independently performed by two investigators. Qualitative synthesis was performed from all included studies and meta-analysis was performed using a random-effects model with inverse variance for studies that reported the concentration of proteins or enzymatic activity. Standardized mean difference (SMD) with respective 95% confidence interval (CI) were calculated for each outcome.ResultsA total of 90 studies (two cohort and 88 cross-sectional designs) of more than 6,000 participants were selected for data extraction, being the quality of evidence graded as "fair" for most of them. The oral cavity of CF individuals presented lower total protein concentration [SMD = 0.37 (95% CI: 0.07-0.68; 18 studies)], lower total antioxidant capacity [SMD = 1.29 (95% CI: 0.74-1.85); 17 studies], and lower carbonic anhydrase activity [SMD = 0.83 (95% CI: 0.58-1.09); three studies], whereas CA individuals presented lower carbonic anhydrase concentration [SMD = −0.66 (95% CI: −1.00 to −0.32); three studies], urease [SMD = −0.95 (IC 95%: −1.72 to −0.17); four studies], and arginine deiminase system [SMD = −2.07 (95% CI: −3.53 to −0.62); three studies] activities. Antimicrobial peptides, secretory immunoglobulin-A concentrations and alpha-amylase activity were similar among individuals.ConclusionDifferences on oral cavity protein abundance were observed among CF and CA individuals. These data indicate some protein patterns for the oral health and dental caries conditions. Even when statistically significant, some of the results were not very consistent. Cohort studies need to be conducted to validate these results.